2020
DOI: 10.1039/d0py00475h
|View full text |Cite
|
Sign up to set email alerts
|

Online tracing of molecular weight evolution during radical polymerization via high-resolution FlowNMR spectroscopy

Abstract: High-resolution FlowNMR was coupled to a continuous flow reactor to monitor polymer molecular weight evolution online by diffusion ordered NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Hence, in the case of a BCP, signals corresponding to different blocks but correlating to the same diffusivity prove that the blocks are indeed connected. [63][64][65][66] A decrease in the diffusion coefficient in comparison with the homopolymers or macroinitiator allows for a qualitative evaluation of an increase in the molecular weight. Loo et al exploited DOSY analysis for mapping the actual molecular weight distribution.…”
Section: Alternative Methods For Molecular Weight Determinationmentioning
confidence: 99%
“…Hence, in the case of a BCP, signals corresponding to different blocks but correlating to the same diffusivity prove that the blocks are indeed connected. [63][64][65][66] A decrease in the diffusion coefficient in comparison with the homopolymers or macroinitiator allows for a qualitative evaluation of an increase in the molecular weight. Loo et al exploited DOSY analysis for mapping the actual molecular weight distribution.…”
Section: Alternative Methods For Molecular Weight Determinationmentioning
confidence: 99%
“…This relation is well established, and has been used in several studies to establish molecular weight calibrations for DOSY experiments in its logarithmic form (see Figure 1). Calibrations for polystyrene, PS, [11a] poly(methyl acrylate), PMA, poly(methyl methacrylate), PMMA, [13] poly(ethylene glycol), PEG, [14] dextrane [10] and pullane [15] have been provided (see Table 1) to date, and DOSY has been used numerous times as a more qualitative tool, especially to prove that two blocks of a block copolymer are joined together chemically. Interestingly, the potential to derive more information than "just" an average molecular weight has also been explored, and Vieville et al demonstrated that DOSY can in principle also correctly measure the dispersity of a sample.…”
Section: Introductionmentioning
confidence: 99%
“…As the complexity of polymeric materials and polymerization processes increases, such as self-assembling block copolymers, sequence-defined polymers, and complex polymerization formulations, the need for effective and facile reaction monitoring becomes more and more important. To address these challenges and meet the requisites for analysis of more complex polymers, Vrijsen et al 169 has implemented high-resolution flow-NMR spectroscopy for monitoring the progress of a polymerization reaction in a continuous flow system. It is important to note that to further test the wealth of data acquired from high-resolution flow-NMR spectroscopy, a previously developed diffusion ordered NMR spectroscopy (DOSY) method was implemented to analyze the molecular weight data of synthesized polymers.…”
Section: Monitoring the Process For Optimization And Scale-upmentioning
confidence: 99%